Edukasi Pencegahan Merokok Siswa Smp Negeri 31 Medan Melalui Penyuluhan Etika Akademik - Ika Putri, Alifyah; Nazwa Panjaitan, Aulia; Wahyuni Manurung, Bela; Hudzaifah Pohan, M. Harits; Nurhayati; Rahmatika Basitu, Tasya (Fakultas Ekonomi Universitas Muhammadiyah Sukabumi, 2025)
Smoking among adolescents, especially junior high school students, is an issue of concern because it risks negative health effects in the long run, as well as hampering their academic and social development. One of the prevention strategies that can be used is through educational activities that are accompanied by the cultivation of academic ethical values. This study aims to provide education about the dangers of smoking through counseling based on academic ethics in order to increase junior high school students' awareness and attitudes towards smoking behavior. This activity was carried out using a qualitative method with a descriptive approach, which aims to explore and deeply understand the behavior and attitudes of SMP Negeri 31 Medan students towards smoking. This method was chosen to provide a rich and contextual understanding of the factors that influence smoking behavior and the effectiveness of prevention education through academic ethics counseling. The results of the counseling showed an increase in students' understanding of the dangers of smoking as well as a more critical attitude towards invitations to smoke from the surrounding environment. Students also showed greater interest in healthy behaviors and ethical values in the school environment. Academic ethics-based education is proven to be effective as a medium of counseling in preventing smoking behavior among junior high school students, because it not only touches the health aspect, but also the ethical values.